2022
DOI: 10.1111/aogs.14449
|View full text |Cite
|
Sign up to set email alerts
|

The relation between body mass index and primary dysmenorrhea: A systematic review and meta‐analysis

Abstract: Introduction The relation between body mass index (BMI) categories and the occurrence of primary dysmenorrhea has been investigated, but the results of these studies are inconsistent and controversial. The aim of our study was to systematically review the literature and investigate the association between each category of BMI and the occurrence of primary dysmenorrhea. Material and methods We conducted a systematic review and meta‐analysis of observational studies related to BMI and primary dysmenorrhea. Eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Their BMI was calculated based on their height and weight. In conformance with previous studies, BMI was defined as underweight, <18.5 kg/m 2 ; normal weight, 18.5 to 23 kg/m 2 ; and overweight: >23 kg/m 2 31,32 ; low BFP was defined as < 22%. 13…”
Section: Methodsmentioning
confidence: 60%
“…Their BMI was calculated based on their height and weight. In conformance with previous studies, BMI was defined as underweight, <18.5 kg/m 2 ; normal weight, 18.5 to 23 kg/m 2 ; and overweight: >23 kg/m 2 31,32 ; low BFP was defined as < 22%. 13…”
Section: Methodsmentioning
confidence: 60%
“…We found that being underweight increases the risk of primary dysmenorrhea. Numerous studies have reported similar results 26,28,29 . An underweight woman may have low body fat, which is necessary for maintaining a normal ovulation cycle.…”
Section: Discussionmentioning
confidence: 75%
“…Numerous studies have reported similar results. 26,28,29 An underweight woman may have low body fat, which is necessary for maintaining a normal ovulation cycle. This can result in excessive secretion of prostaglandins and irregular ovulation cycles, increasing the risk of primary dysmenorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous studies regarding the relation between BMI and PD are inconsistent and controversial [30], which need to be con rmed in future studies. In addition, the relation between TaqI (rs731236) and PD needs further studies.…”
Section: The Taqi Genotypes and Its Relation To Serum 25(oh)d And Pdmentioning
confidence: 93%
“…Although, a meta-analysis reported an increased risk of PD in underweight women compared to overweight and obese women [30].…”
Section: The Taqi Genotypes and Its Relation To Serum 25(oh)d And Pdmentioning
confidence: 95%